2010
DOI: 10.1097/mao.0b013e3181bc3781
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Inflammation in the Middle Ear Induces Deterioration of Bone-Conduction Hearing Level in Patients With Eosinophilic Otitis Media

Abstract: Eosinophilic-inflammation-related substances such as ECP and IgE are closely related to the deterioration of BCHL at high frequencies. Particularly, IgE concentration in MEE is a good indicator of BCHL elevation. We should always pay attention to the hearing acuity of EOM patients with the risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 12 publications
(14 reference statements)
0
18
0
5
Order By: Relevance
“…High-tone loss was more frequently encountered and more severe in EOM patients than in age-matched patients with chronic otitis media (20). Our previous study also showed that the concentration of IgE in MEE was significantly and positively correlated with the BCHLs at 2 and 4 kHz and that a high concentration of IgE in the MEE as well as a high serum IgE level were significant risk factors for BCHL deterioration in EOM patients (7). Therefore, anti-IgE therapy can prevent BCHL deterioration.…”
Section: Anti-ige Therapy Was First Included Inmentioning
confidence: 83%
See 1 more Smart Citation
“…High-tone loss was more frequently encountered and more severe in EOM patients than in age-matched patients with chronic otitis media (20). Our previous study also showed that the concentration of IgE in MEE was significantly and positively correlated with the BCHLs at 2 and 4 kHz and that a high concentration of IgE in the MEE as well as a high serum IgE level were significant risk factors for BCHL deterioration in EOM patients (7). Therefore, anti-IgE therapy can prevent BCHL deterioration.…”
Section: Anti-ige Therapy Was First Included Inmentioning
confidence: 83%
“…In addition, many IgE-immunopositive cells are found in the middle ear mucosa (4). In the middle ear effusion (MEE), the IgE levels are significantly higher in EOM patients than in control patients with common otitis media with effusion (7). The presence of high levels of IgE may exacerbate eosinophilic inflammation in the middle ear.…”
mentioning
confidence: 98%
“…To identify EOM in cases of NP could entail watching patients more closely. Indeed, an increased incidence of progressive and/or sudden sensorineural hearing loss had been described in cases of EOM [24], with bacterial infection and inflammatory mediators released in the middle ear contributing to inner ear damage [25]. This bone conduction hearing loss sometimes can lead to profound deafness.…”
Section: Otitis Media With Effusion In Nasal Polyposis: How To Manage?mentioning
confidence: 98%
“…High-tone hearing loss, in particular, is more frequent and more severe in EOM patients than in COM patients [7], with 47% of EOM patients showing deterioration in BCHL, and 6% developing bilateral profound hearing loss according to the clinical survey of EOM in Japan [4]. The cause of deterioration in BCHL in cases of EOM remains unclear, but significantly higher concentrations of eosinophil cationic protein (ECP) and IgE have been detected in the middle ear effusion of EOM patients than in that of control patients [8]. Further, numerous eosinophil infiltrations were in the scala tympani, as well as severe morphological damage to the cochlea, the organ of Corti and the stria vascularis was observed in the prolonged topical stimulation animal model and is thought to be the cause of the deterioration in BCHL [9].…”
Section: Discussionmentioning
confidence: 99%